Two isomeric compounds from Streptomyces species and their antimicrobial activity - Zakia Sultana Sathi; Md. Anwar Habib; Abu Syed Md. Anisuzzaman; Md. Anwarul Islam (Bangladesh Pharmacological Society, 2010)
The chloroform extract of the culture filtrate of an isolated Streptomyces species upon chromatographic analysis had lead to the isolation of two isomeric compounds (I and II). The structure of the compounds was considered to be Stretomysone A (I) and Streptomysone B (II) by its spectral data. Both the compounds showed significant antimicrobial activity against tested pathogenic bacteria and fungus. The compounds seem to be first report of isomeric compound from Streptomyces species having antimicrobial activity.